Community Immersion, Trust-Building, and Recruitment among Hard to Reach Populations: A Case Study of Muslim Women in Detroit Metro Area - Mohebbi Mehrsa, Mehri; Linders, Annulla; Chifos, Carla (Qualitative Sociology Review, 2018)
Scholars have identified a range of factors that influence the ability of researchers to access hard-toreach groups and the willingness of their members to participate in research. In this paper, we draw on insights from both ethnographic methods and participatory action research to demonstrate the importance of building trust in our relationships with hard-to-reach participants in research based on interviews. Such trust-building, we show, is greatly facilitated by pre-recruitment immersion that aids not only the recruitment of individual participants but also improves the quality of the data collected. These methodological concerns emerged from an interview study focusing on Muslim women’s use of urban public recreational spaces in South-East Michigan. Although the first author of this paper, as a woman and a Muslim, is a formal insider in the study population, her experiences with recruitment demonstrate that the access granted by insider status is insufficient as grounds for a research relationship based on trust. This is so especially when the target population is as marginalized and embattled as the post 9/11 immigrant Muslim community. With more than two years of community immersion, however, she was able to foster enough trust to secure a large number of committed participants that spoke freely and thoughtfully about the issues at stake (78 in all).